Gambaran Kejadian Infeksi Bayi Baru Lahir di Bagian Perinatologi RSUP Dr.M.Djamil Padang Tahun 2012: Overview of Newborn Infection Incidence in the Perinatology Department of Dr.M.Djamil Padang Hospital in 2012 - Irvina Meliya; Vetty Priscilla (NERS Jurnal Keperawatan, 2013)
Infection is one of the contributed factors of neonatal morbidity and mortality in the world. Infection in neonatal were divided into two groups. There were major infection (neonatal sepsis, meningitis, neonatal pneumonia, urinary tract infection, acute osteitis, neonatal tetanus) and minor infections (omphalitis, pemphigus neonatorum, ophthalmia neonatorum, moniliasis, stomatitis). The purpose of this study was to see description of the neonatal incidence infection in perinatology unit at Dr.M.Djamil Padang Hospital in 2012. The design was a descriptive study by using retrospective at the medical records department with a check list. The samples were 262 newborn. The results were analyzed by univariate and it showed that 78.6% of babies was suffered from major infections. Based on the result, it is sugested to mother in order to pay attention to their health and their nutrition during pregnancy. So, it can reduce the preterm pregnancies, which is one of predisposition factors of infection. Thus, increasing precaution steps of infection to the newborn for the health personnel.